Updated checklist of the ice-crawlers (Insecta: Grylloblattodea: Grylloblattidae) of North America, with notes on their natural history, biogeography and conservation - Schoville, Sean D.; Graening, G. O. (Zootaxa, 2013)
We provide an updated checklist and comprehensive distributional record of Grylloblatta (Grylloblattodea: Grylloblattidae) in North America. These distribution records are based upon a thorough review of the literature, as well as unpublished data of the authors and colleagues. Thirteen species of Grylloblatta are currently described, with up to 16 additional taxa awaiting formal description. Distributional data shows that endemism of Grylloblatta is high and geographic range size is typically small: the median geographical area of 13 species and six putative species is 179 km2. It is clear that there is a general lack of knowledge of species range limits and local population sizes; for example, three Grylloblatta species are known from just a single locality and less than 15 specimens each. Conservation status ranks are suggested in order to update the IUCN Red List and national Natural Heritage Network Database. Finally, we describe the natural history and seasonality of Grylloblatta, discuss their unique biogeography, and provide recommendations for future surveys of grylloblattid species by highlighting known distributional gaps.